Eye tracking as a research method applied to communication sciences - Barreto, Ana Margarida (2012)
Although it is not considered a novelty, the knowledge of eye tracking technology as a method of collecting and analyzing information, as well as its implementation potential in different areas of academic, scientific and commercial area are still in its infancy. For this reason has raised the interest in developing a study able to inform about this technology, both researchers and professionals of communication sciences, succinctly and clearly. Therefore, the topics covered during the present study were selected for being the for anyone wishing to understand how this research tool works. They are the following: the origin of the technology and its description; project design; challenges in sample selection; collection, interpretation and analysis, and present limitations.